Balance in Life and Declining Marginal Utility of Diverse Resources - DIENER, Ed (Institutional Knowledge at Singapore Management University, 2008)
Declining marginal utility (DMU) describes the reduced value that additional units of money or consumer goods have in comparison to units acquired earlier. We extend this idea to social resources and activities such as socializing time, free time, and number of children, suggesting that most resources will show DMU as the person experiences more of them. In Study 1, participants reported how many years of adult life they would sacrifice to have increasingly more of each resource or activity. Income showed declining marginal utility, but other goods showed an ideal-level pattern in which they were valued less after an optimal amount. In Phase 2 of Study 1, we assessed the mix of activities people most prefer. Participants rated the desirability of various combinations of time spent in different activities. Spending all of one’s free time in a pleasant activity was not as desirable as spending some of the time in other desirable, but less enjoyable, activities. In Study 2, we used a representative sample of the world to assess people’s affect balance (positive minus negative moods) on the previous day, along with how much time they spent in activities such as socializing with family and friends. The most popular activity was socializing with family and friends, but even here there was DMU for more hours of this behavior. We also analyzed several forms of well-being in reference to household income. Income showed a clear DMU pattern using daily moods as the outcome, as well as for life evaluations and satisfaction with standard of living. The results of the two studies explain why people do not pursue happiness by spending all of their time in the most pleasant activities, such as socializing, but instead choose a mixture of activities. A desire for balance in human activities and resources has important implications for the structure of the workplace, leisure time, work hours, and other important domains of life.